La representación social como vinculación entre agentes sociales y el espacio urbano en el distrito central de Barva, Heredia, Costa Rica - Otárola Guevara, Marcela (2015)
This article shows the link between social partners and the urban space in the community of Barva, throughthe exposure of social representations that prevail in the mentality of its inhabitants and are projected in the configuration of the city. The action of these agents affects the physical and symbolic morphology of the city, transforming it.